2023
DOI: 10.1021/acsabm.3c00205
|View full text |Cite
|
Sign up to set email alerts
|

Injectable In Situ Photocrosslinked Hydrogel Dressing for Infected Wound Healing

Abstract: A traditional injectable photocrosslinked hydrogel had disadvantages of the residual photoinitiator and toxic crosslinker, slow in situ curing, and a complex preparation process. At the same time, hydrogels cannot act as artificial skin to restore skin sensory function during the wound healing cycle. In this work, an injectable photocrosslinked hydrogel was prepared which can be quickly in situ cured without photoinitiator. Oxidized sodium alginate was used as a natural macromolecular crosslinking agent to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“… 57 Recently, Zhang et al reported the direct conjugation of the styrylpyridinium small molecule photoinitiator dye to polyvinyl alcohol (PVA) (15% wt/vol) to develop a photocuring, injectable hydrogel in complex with oxidized sodium alginate. 58 The material was evaluated in an S. aureus ‐infected full‐thickness wound model in mice with in situ photoactivation of dressing‐to‐wound interaction at 365 nm for 30 s. Subsequent differential irradiation of incorporated polydopamine with 808‐nm light for 10 min demonstrated a significant acceleration of wound closure with the hydrogel alone that was further enhanced by NIR stimulation, accompanied by enhanced angiogenesis and collagen deposition in proportion to the healing efficacy. 58 …”
Section: Uv Light‐activated Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“… 57 Recently, Zhang et al reported the direct conjugation of the styrylpyridinium small molecule photoinitiator dye to polyvinyl alcohol (PVA) (15% wt/vol) to develop a photocuring, injectable hydrogel in complex with oxidized sodium alginate. 58 The material was evaluated in an S. aureus ‐infected full‐thickness wound model in mice with in situ photoactivation of dressing‐to‐wound interaction at 365 nm for 30 s. Subsequent differential irradiation of incorporated polydopamine with 808‐nm light for 10 min demonstrated a significant acceleration of wound closure with the hydrogel alone that was further enhanced by NIR stimulation, accompanied by enhanced angiogenesis and collagen deposition in proportion to the healing efficacy. 58 …”
Section: Uv Light‐activated Materialsmentioning
confidence: 99%
“… 58 The material was evaluated in an S. aureus ‐infected full‐thickness wound model in mice with in situ photoactivation of dressing‐to‐wound interaction at 365 nm for 30 s. Subsequent differential irradiation of incorporated polydopamine with 808‐nm light for 10 min demonstrated a significant acceleration of wound closure with the hydrogel alone that was further enhanced by NIR stimulation, accompanied by enhanced angiogenesis and collagen deposition in proportion to the healing efficacy. 58 …”
Section: Uv Light‐activated Materialsmentioning
confidence: 99%
“…Many materials have been developed to prepare injectable hydrogel wound dressings, such as natural polymers (gelatin, chitosan, , alginate, , fibrin, , etc.) and synthetic polymers (poly­(vinyl alcohol), , poly­(acrylic acid), etc.). In these studies, methacrylate-based gelatin (GelMA) is favored by a wide range of scholars for its outstanding biocompatibility, biodegradability, and excellent moldability as well as rapid gelation performance. , Wang et al have developed a methacrylation gelatin/oxidized dextran hydrogel in combination with highly dispersed amino-modified poly­(lactic- co -glycolic acid) electrospun fiber segments.…”
Section: Introductionmentioning
confidence: 99%
“…(2) The initiation efficiency of the initiator is not enough, and the speed of its in situ molding is not enough. (3) The adhesion to the trauma surface and the mechanical properties are relatively weak. , Thus, it is relevant to develop injectable hydrogels that can be molded in situ with good biocompatibility, mechanical properties, and adhesion performance.…”
Section: Introductionmentioning
confidence: 99%